Evolving role of minimally invasive techniques in the management of symptomatic bone metastases. Issue 2 (June 2021) - Benhabib, Hadas; Meirovich, Harley; David, Elizabeth
Abstract : Purpose of review: Bone metastases are responsible for considerable morbidity, which can significantly limit a patient's quality of life. This article aims to review minimally invasive, image-guided locoregional treatments for symptomatic bone metastases as an adjunct to conventional treatment modalities. Recent findings: Conservative therapy and radiation therapy (RT) can be effective at addressing pain, however, they require time to achieve optimal efficacy and do not address the instability and progressive collapse of pathological fractures. Vertebral and pelvic augmentation with cement enhances structural stability and can prevent progressive collapse and deformity. Ablative therapies, including radiofrequency ablation (RFA), cryoablation, and photodynamic therapy (PDT), induce cellular destruction of tumor tissue. RFA and PDT can be combined with cement augmentation in a single sitting. Summary: Minimally invasive image-guided treatments can provide rapid pain relief, enhance mechanical stability, and improve quality of life. These treatments are associated with low complication rates and are suitable for frail patients. They can be used as companion procedures to conventional treatments, or function as an alternative for patients with radioresistant biologies or those with dose limitations from prior RT sessions.